Sistem Informasi Pengelolaan Arsip Digital Pada Kantor Dinas Pertanian Provinsi Aceh Berbasis Web - Naja, Saifinatun; Akbar, Rizaldi; Ismail (Jurnal Sistem Komputer (SISKOM), 2024)
This research explores the implementation of a web-based Digital Records Management Information System at the Aceh Provincial Agriculture Service Office. The waterfall approach is used as a framework for developing this system, which involves a series of stages starting from requirements analysis to maintenance. The main focus is designing a responsive and user-friendly user interface, which allows users to interact with the system optimally. The features included, such as Login Page, Home Page, Mail Transactions, Agenda Book, File/Document Gallery, Document Reference, and Settings, are designed to meet archive management needs efficiently. Test results validate the suitability of the system with established expectations and needs. Through the implementation of Digital Archives, the aim is to increase effectiveness, efficiency, transparency and accuracy in managing information related to budget realization at the Aceh Provincial Agriculture Service. Suggestions for improvement include user training, evaluation of application usage, development of additional features, data security improvements, and maintenance support. In this way, Digital Archives is expected to make a significant contribution in increasing the efficiency of archive management within government agencies, such as the Aceh Provincial Agriculture Service, and provide a model that is suitable for adoption by similar institutions.